2020
DOI: 10.18805/ag.d-189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Intake of Moringa oleifera Leaf Meal on The Growth Performance of Pullet Chicks

Abstract: This study determined the effects of dietary intake of Moringa Oleifera (M. oleifera) leaf meal on growth performance of pullets. Two hundred and forty Isa Brown day-old chicks were randomly allotted to 4 different treatment groups and each treatment had 3 replicates of 20 chicks each. At 4th week of age, birds in group 1 (T1)were fed with 16% crude protein (CP) grower diet (control feed; 0.0% M. oleifera) whereas birds in groups 2 (T2), 3 (T3) and 4 (T4) received the control feed supplemented with 2.5%; 5.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The result was in line with Sy and Thu (2015), who state that M. oleifera leaf meal achieved higher daily weight gain in broilers than the control while the lowest FCR was recorded in the control group. However, FCR was found to decrease progressively with the increased inclusion of M. oleifera leaf meal in pullet diet (Ugwuoke et al, 2020). The inclusion of M. oleifera leaf meal was found to improve body weight, feed conversion efficiency, feed intake and protein efficiency of layer birds (Ojha et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The result was in line with Sy and Thu (2015), who state that M. oleifera leaf meal achieved higher daily weight gain in broilers than the control while the lowest FCR was recorded in the control group. However, FCR was found to decrease progressively with the increased inclusion of M. oleifera leaf meal in pullet diet (Ugwuoke et al, 2020). The inclusion of M. oleifera leaf meal was found to improve body weight, feed conversion efficiency, feed intake and protein efficiency of layer birds (Ojha et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The study was carried out in the 2018 and 2019 early planting seasons at the Department of Agricultural Education demonstration farm, University of Nigeria, Nsukka located at 6.84  N, 7.37  E (Ugwuoke, et al, 2020). The study adopted experimental research based on a split-plot design which was replicated thrice.…”
Section: Methodsmentioning
confidence: 99%
“…Findings from various studies have shown that medicinal plants improve the productive performance of birds [1,2,3,4]), pullet chicks [5], rabbits [6,7], extends the shelf-life of stored meat products [8,9], in addition to their overall promise of enhancing public health.…”
Section: Introductionmentioning
confidence: 99%